Pengaruh Layanan Mobile Banking terhadap Kepuasan Nasabah PT. Bank Muamalat Indonesia, Tbk Kantor Cabang Stabat - Wahyudi, Deddy; Afif, Yaumul Khair; Khairunnisa, Khairunnisa (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine the effect of Mobile Banking services on customer satisfaction, the magnitude of the influence of Mobile Banking services on customer satisfaction, and the relationship between Mobile Banking services on customer satisfaction PT. Bank Muamalat Indonesia, Tbk Stabat Branch Office. This type of research is quantitative research that emphasizes numerical data (numbers) processed using inferential statistical methods (analyzing the relationship between variables by testing hypotheses). The source of this research data was obtained from the answers to the questionnaire given by the research respondents, namely customers who use the Mobile Banking service of PT. Bank Muamalat Indonesia, Tbk Stabat Branch Office, totaling 75 respondents. Data processing and analysis in this study used the SPSS computer program and Microsoft Office Excel. The results of the study explain that there is a significant influence between Mobile Banking services on customer satisfaction, this is obtained from statistical results showing a significance value of 0.000 and tcount of 10.425. Based on this, it can be argued that α (0.000 0.05) and tcount ttable (10.425 1.99300) means that there is an influence of variable X on Y. The Mobile Banking services offered by PT. Bank Muamalat Indonesia, Tbk Stabat Branch Office affects customer satisfaction by 59.3%. There is a positive or parallel relationship between Mobile Banking services and PT. Bank Muamalat Indonesia, Tbk Stabat Branch Office.